(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The article examines an overview of the era of ancient Turkic monuments from the point of view of the emergence of the first types of writing from the origin of the Turkic (rune-like) writing until the adoption of Arabic script. The influence of ethnocultural and ethnoconfessional conditions on the emergence and development of Sogdian writing is considered.